Factors Affecting Transfer of On-The-Job Training at Workplaces in Pakistan - Fatima, Maham; Siddiqui, Danish Ahmed (Asian Business Review, 2020)
Purpose: This research is focused on examining the factors that influence transfer (effectiveness) of On-The-Job training at workplaces in Pakistan. The study identifies the factors that affect transfer of OJT training included independent variables such as motivation to learn, Perceived Organizational Support and Training Design and their impact on employees’ performance i.e. Transfer of Training.Methodology: The study adopted quantitative research and data was collected through well-structured questionnaire. The sample of 200 participants were selected throughout Pakistan using convenience sampling technique. Smart PLS software was used to analyse the data through descriptive statistics, structural equation modelling and Confirmatory factor analysis.Findings: The result revealed that there is a strong and significant impact of motivation to learn and training design on transfer of OJT training at workplaces in Pakistan. However, the results do not show any significant impact of Perceived Organizational Support in organizations on transfer of OJT training.Conclusions: This shows that even though, if the organization support is not present, the motivation to learn new things and to implement it to the workplace and effectively designed training programs can overcome the issues.Practical Implications: Organizations can use the result in favour of their organizational effectiveness, to consistently design effective training programs, and to consistently motivate their employees and to improve support and guidance by top management in the organizations.